Women in STEM: Academic Productions in the Brazilian Context - Arndt, Gilmara Joanol (2023)
The low number of women in the so-called STEM fields has been the subject of research around the world. Such investigations are important for expanding the discussion and reflection on the disparity between the number of men and women in these areas. With this in mind, this article seeks to contribute to an understanding of the Brazilian academic scenario regarding the participation of women in the STEM (world of) work. Thus, the question that guided our mapping was: what is the national production on women’s participation in the Brazilian STEM scene? To this end, we searched the following databases: SCOPUS, Web of Science, Google Scholar and Scielo, and found a total of 47 references. These were analyzed and separated into six groups according to their central proposal.